mathlib documentation

data.sum.basic

Disjoint union of types #

This file proves basic results about the sum type α ⊕ β.

α ⊕ β is the type made of a copy of α and a copy of β. It is also called disjoint union.

Main declarations #

Notes #

The definition of sum takes values in Type*. This effectively forbids Prop- valued sum types. To this effect, we have psum, which takes value in Sort* and carries a more complicated universe signature in consequence. The Prop version is or.

@[protected, instance]
def sum.decidable_eq (α : Type u) [a : decidable_eq α] (β : Type v) [a_1 : decidable_eq β] :
@[simp]
theorem sum.forall {α : Type u} {β : Type v} {p : α β → Prop} :
(∀ (x : α β), p x) (∀ (a : α), p (sum.inl a)) ∀ (b : β), p (sum.inr b)
@[simp]
theorem sum.exists {α : Type u} {β : Type v} {p : α β → Prop} :
(∃ (x : α β), p x) (∃ (a : α), p (sum.inl a)) ∃ (b : β), p (sum.inr b)
theorem sum.inl_injective {α : Type u} {β : Type v} :
theorem sum.inr_injective {α : Type u} {β : Type v} :
@[simp]
def sum.get_left {α : Type u} {β : Type v} :
α βoption α

Check if a sum is inl and if so, retrieve its contents.

Equations
@[simp]
def sum.get_right {α : Type u} {β : Type v} :
α βoption β

Check if a sum is inr and if so, retrieve its contents.

Equations
@[simp]
def sum.is_left {α : Type u} {β : Type v} :
α βbool

Check if a sum is inl.

Equations
@[simp]
def sum.is_right {α : Type u} {β : Type v} :
α βbool

Check if a sum is inr.

Equations
theorem sum.get_left_eq_none_iff {α : Type u} {β : Type v} {x : α β} :
theorem sum.get_right_eq_none_iff {α : Type u} {β : Type v} {x : α β} :
@[protected]
def sum.map {α : Type u} {α' : Type w} {β : Type v} {β' : Type x} (f : α → α') (g : β → β') :
α βα' β'

Map α ⊕ β to α' ⊕ β' sending α to α' and β to β'.

Equations
@[simp]
theorem sum.map_inl {α : Type u} {α' : Type w} {β : Type v} {β' : Type x} (f : α → α') (g : β → β') (x : α) :
sum.map f g (sum.inl x) = sum.inl (f x)
@[simp]
theorem sum.map_inr {α : Type u} {α' : Type w} {β : Type v} {β' : Type x} (f : α → α') (g : β → β') (x : β) :
sum.map f g (sum.inr x) = sum.inr (g x)
@[simp]
theorem sum.map_map {α : Type u} {α' : Type w} {β : Type v} {β' : Type x} {α'' : Type u_1} {β'' : Type u_2} (f' : α' → α'') (g' : β' → β'') (f : α → α') (g : β → β') (x : α β) :
sum.map f' g' (sum.map f g x) = sum.map (f' f) (g' g) x
@[simp]
theorem sum.map_comp_map {α : Type u} {α' : Type w} {β : Type v} {β' : Type x} {α'' : Type u_1} {β'' : Type u_2} (f' : α' → α'') (g' : β' → β'') (f : α → α') (g : β → β') :
sum.map f' g' sum.map f g = sum.map (f' f) (g' g)
@[simp]
theorem sum.map_id_id (α : Type u_1) (β : Type u_2) :
theorem sum.inl.inj_iff {α : Type u} {β : Type v} {a b : α} :
theorem sum.inr.inj_iff {α : Type u} {β : Type v} {a b : β} :
theorem sum.inl_ne_inr {α : Type u} {β : Type v} {a : α} {b : β} :
theorem sum.inr_ne_inl {α : Type u} {β : Type v} {a : α} {b : β} :
@[protected]
def sum.elim {α : Type u_1} {β : Type u_2} {γ : Sort u_3} (f : α → γ) (g : β → γ) :
α β → γ

Define a function on α ⊕ β by giving separate definitions on α and β.

Equations
Instances for sum.elim
@[simp]
theorem sum.elim_inl {α : Type u_1} {β : Type u_2} {γ : Sort u_3} (f : α → γ) (g : β → γ) (x : α) :
sum.elim f g (sum.inl x) = f x
@[simp]
theorem sum.elim_inr {α : Type u_1} {β : Type u_2} {γ : Sort u_3} (f : α → γ) (g : β → γ) (x : β) :
sum.elim f g (sum.inr x) = g x
@[simp]
theorem sum.elim_comp_inl {α : Type u_1} {β : Type u_2} {γ : Sort u_3} (f : α → γ) (g : β → γ) :
@[simp]
theorem sum.elim_comp_inr {α : Type u_1} {β : Type u_2} {γ : Sort u_3} (f : α → γ) (g : β → γ) :
@[simp]
theorem sum.elim_inl_inr {α : Type u_1} {β : Type u_2} :
theorem sum.comp_elim {α : Type u_1} {β : Type u_2} {γ : Sort u_3} {δ : Sort u_4} (f : γ → δ) (g : α → γ) (h : β → γ) :
f sum.elim g h = sum.elim (f g) (f h)
@[simp]
theorem sum.elim_comp_inl_inr {α : Type u_1} {β : Type u_2} {γ : Sort u_3} (f : α β → γ) :
theorem sum.elim_comp_map {α : Type u_1} {β : Type u_2} {γ : Type u_3} {δ : Type u_4} {ε : Sort u_5} {f₁ : α → β} {f₂ : β → ε} {g₁ : γ → δ} {g₂ : δ → ε} :
sum.elim f₂ g₂ sum.map f₁ g₁ = sum.elim (f₂ f₁) (g₂ g₁)
@[simp]
theorem sum.update_elim_inl {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq α] [decidable_eq β)] {f : α → γ} {g : β → γ} {i : α} {x : γ} :
@[simp]
theorem sum.update_elim_inr {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq β] [decidable_eq β)] {f : α → γ} {g : β → γ} {i : β} {x : γ} :
@[simp]
theorem sum.update_inl_comp_inl {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq α] [decidable_eq β)] {f : α β → γ} {i : α} {x : γ} :
@[simp]
theorem sum.update_inl_apply_inl {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq α] [decidable_eq β)] {f : α β → γ} {i j : α} {x : γ} :
@[simp]
theorem sum.update_inl_comp_inr {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq β)] {f : α β → γ} {i : α} {x : γ} :
@[simp]
theorem sum.update_inl_apply_inr {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq β)] {f : α β → γ} {i : α} {j : β} {x : γ} :
@[simp]
theorem sum.update_inr_comp_inl {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq β)] {f : α β → γ} {i : β} {x : γ} :
@[simp]
theorem sum.update_inr_apply_inl {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq β)] {f : α β → γ} {i : α} {j : β} {x : γ} :
@[simp]
theorem sum.update_inr_comp_inr {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq β] [decidable_eq β)] {f : α β → γ} {i : β} {x : γ} :
@[simp]
theorem sum.update_inr_apply_inr {α : Type u} {β : Type v} {γ : Type u_1} [decidable_eq β] [decidable_eq β)] {f : α β → γ} {i j : β} {x : γ} :
@[simp]
def sum.swap {α : Type u} {β : Type v} :
α ββ α

Swap the factors of a sum type

Equations
@[simp]
theorem sum.swap_swap {α : Type u} {β : Type v} (x : α β) :
x.swap.swap = x
@[simp]
theorem sum.swap_swap_eq {α : Type u} {β : Type v} :
@[simp]
theorem sum.swap_left_inverse {α : Type u} {β : Type v} :
@[simp]
theorem sum.swap_right_inverse {α : Type u} {β : Type v} :
inductive sum.lift_rel {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} (r : α → γ → Prop) (s : β → δ → Prop) :
α βγ δ → Prop
  • inl : ∀ {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s : β → δ → Prop} {a : α} {c : γ}, r a csum.lift_rel r s (sum.inl a) (sum.inl c)
  • inr : ∀ {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s : β → δ → Prop} {b : β} {d : δ}, s b dsum.lift_rel r s (sum.inr b) (sum.inr d)

Lifts pointwise two relations between α and γ and between β and δ to a relation between α ⊕ β and γ ⊕ δ.

Instances for sum.lift_rel
@[simp]
theorem sum.lift_rel_inl_inl {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s : β → δ → Prop} {a : α} {c : γ} :
sum.lift_rel r s (sum.inl a) (sum.inl c) r a c
@[simp]
theorem sum.not_lift_rel_inl_inr {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s : β → δ → Prop} {a : α} {d : δ} :
@[simp]
theorem sum.not_lift_rel_inr_inl {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s : β → δ → Prop} {b : β} {c : γ} :
@[simp]
theorem sum.lift_rel_inr_inr {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s : β → δ → Prop} {b : β} {d : δ} :
sum.lift_rel r s (sum.inr b) (sum.inr d) s b d
@[protected, instance]
def sum.lift_rel.decidable {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s : β → δ → Prop} [Π (a : α) (c : γ), decidable (r a c)] [Π (b : β) (d : δ), decidable (s b d)] (ab : α β) (cd : γ δ) :
Equations
theorem sum.lift_rel.mono {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r₁ r₂ : α → γ → Prop} {s₁ s₂ : β → δ → Prop} {x : α β} {y : γ δ} (hr : ∀ (a : α) (b : γ), r₁ a br₂ a b) (hs : ∀ (a : β) (b : δ), s₁ a bs₂ a b) (h : sum.lift_rel r₁ s₁ x y) :
sum.lift_rel r₂ s₂ x y
theorem sum.lift_rel.mono_left {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r₁ r₂ : α → γ → Prop} {s : β → δ → Prop} {x : α β} {y : γ δ} (hr : ∀ (a : α) (b : γ), r₁ a br₂ a b) (h : sum.lift_rel r₁ s x y) :
sum.lift_rel r₂ s x y
theorem sum.lift_rel.mono_right {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s₁ s₂ : β → δ → Prop} {x : α β} {y : γ δ} (hs : ∀ (a : β) (b : δ), s₁ a bs₂ a b) (h : sum.lift_rel r s₁ x y) :
sum.lift_rel r s₂ x y
@[protected]
theorem sum.lift_rel.swap {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s : β → δ → Prop} {x : α β} {y : γ δ} (h : sum.lift_rel r s x y) :
@[simp]
theorem sum.lift_rel_swap_iff {α : Type u} {β : Type v} {γ : Type u_1} {δ : Type u_2} {r : α → γ → Prop} {s : β → δ → Prop} {x : α β} {y : γ δ} :
inductive sum.lex {α : Type u} {β : Type v} (r : α → α → Prop) (s : β → β → Prop) :
α βα β → Prop
  • inl : ∀ {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} {a₁ a₂ : α}, r a₁ a₂sum.lex r s (sum.inl a₁) (sum.inl a₂)
  • inr : ∀ {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} {b₁ b₂ : β}, s b₁ b₂sum.lex r s (sum.inr b₁) (sum.inr b₂)
  • sep : ∀ {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} (a : α) (b : β), sum.lex r s (sum.inl a) (sum.inr b)

Lexicographic order for sum. Sort all the inl a before the inr b, otherwise use the respective order on α or β.

Instances for sum.lex
@[simp]
theorem sum.lex_inl_inl {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} {a₁ a₂ : α} :
sum.lex r s (sum.inl a₁) (sum.inl a₂) r a₁ a₂
@[simp]
theorem sum.lex_inr_inr {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} {b₁ b₂ : β} :
sum.lex r s (sum.inr b₁) (sum.inr b₂) s b₁ b₂
@[simp]
theorem sum.lex_inr_inl {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} {a : α} {b : β} :
@[protected]
theorem sum.lift_rel.lex {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} {a b : α β} (h : sum.lift_rel r s a b) :
sum.lex r s a b
theorem sum.lex.mono {α : Type u} {β : Type v} {r₁ r₂ : α → α → Prop} {s₁ s₂ : β → β → Prop} {x y : α β} (hr : ∀ (a b : α), r₁ a br₂ a b) (hs : ∀ (a b : β), s₁ a bs₂ a b) (h : sum.lex r₁ s₁ x y) :
sum.lex r₂ s₂ x y
theorem sum.lex.mono_left {α : Type u} {β : Type v} {r₁ r₂ : α → α → Prop} {s : β → β → Prop} {x y : α β} (hr : ∀ (a b : α), r₁ a br₂ a b) (h : sum.lex r₁ s x y) :
sum.lex r₂ s x y
theorem sum.lex.mono_right {α : Type u} {β : Type v} {r : α → α → Prop} {s₁ s₂ : β → β → Prop} {x y : α β} (hs : ∀ (a b : β), s₁ a bs₂ a b) (h : sum.lex r s₁ x y) :
sum.lex r s₂ x y
theorem sum.lex_acc_inl {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} {a : α} (aca : acc r a) :
acc (sum.lex r s) (sum.inl a)
theorem sum.lex_acc_inr {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} (aca : ∀ (a : α), acc (sum.lex r s) (sum.inl a)) {b : β} (acb : acc s b) :
acc (sum.lex r s) (sum.inr b)
theorem sum.lex_wf {α : Type u} {β : Type v} {r : α → α → Prop} {s : β → β → Prop} (ha : well_founded r) (hb : well_founded s) :
theorem function.injective.sum_elim {α : Type u} {β : Type v} {γ : Type u_1} {f : α → γ} {g : β → γ} (hf : function.injective f) (hg : function.injective g) (hfg : ∀ (a : α) (b : β), f a g b) :
theorem function.injective.sum_map {α : Type u} {α' : Type w} {β : Type v} {β' : Type x} {f : α → β} {g : α' → β'} (hf : function.injective f) (hg : function.injective g) :
theorem function.surjective.sum_map {α : Type u} {α' : Type w} {β : Type v} {β' : Type x} {f : α → β} {g : α' → β'} (hf : function.surjective f) (hg : function.surjective g) :

Ternary sum #

Abbreviations for the maps from the summands to α ⊕ β ⊕ γ. This is useful for pattern-matching.

@[simp]
def sum3.in₀ {α : Type u} {β : Type v} {γ : Type u_1} (a : α) :
α β γ

The map from the first summand into a ternary sum.

Equations
@[simp]
def sum3.in₁ {α : Type u} {β : Type v} {γ : Type u_1} (b : β) :
α β γ

The map from the second summand into a ternary sum.

Equations
@[simp]
def sum3.in₂ {α : Type u} {β : Type v} {γ : Type u_1} (c : γ) :
α β γ

The map from the third summand into a ternary sum.

Equations